2015
DOI: 10.21083/partnership.v10i1.3338
|View full text |Cite
|
Sign up to set email alerts
|

Silent and Independent: Student Use of Academic Library Study Space

Abstract: In the fall of 2012, Concordia University Libraries started planning for renovations which would result in the increase of study spaces in one of its two libraries and the reduction at the other. In order to maximize the functionality of the reduced study space footprint, a survey and focus groups were used to better understand the specific space needs of the library's campus community. The study revealed differences in the use of the library among the respondents from different programs of study. Respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
5
14
0
Order By: Relevance
“…(p. 219) from others. Similar research also notes individual study carrels and quiet spaces are valued (Hall & Kapa, 2015;Montgomery & Miller, 2011;Ojennus & Watts, 2017;Oliveira, 2016).…”
Section: Space Attributessupporting
confidence: 54%
See 1 more Smart Citation
“…(p. 219) from others. Similar research also notes individual study carrels and quiet spaces are valued (Hall & Kapa, 2015;Montgomery & Miller, 2011;Ojennus & Watts, 2017;Oliveira, 2016).…”
Section: Space Attributessupporting
confidence: 54%
“…Montgomery (2014) refers to the library as a place for informal learning, where students can set their own goals and determine their needs. The library is thought of for its study spaces and less for services and collections (DeClercq & Cranz, 2014;Hall and Kapa, 2015). A place to gather and have conversations, according to Oldenburg (1997), is an important part of learning; the library has begun to be this place.…”
Section: Library As Placementioning
confidence: 99%
“…Other items discussed by students as key to improving the library were to increase the number of electrical outlets, to improve the Wi-Fi signal throughout the entire building, and to offer wireless and free printing. Hall and Kapa (2015) found similar requests from library users for larger table space, additional comfortable furniture, and an increased number of desktop computers. Other recent qualitative and mixed-methods assessments of library space use have come to similar conclusions regarding the need for access to electrical power, sufficient group study space, and flexible seating (Asher, 2017;Dominguez, 2016;McCrary, 2017).…”
Section: Student Use Of Library Spacementioning
confidence: 66%
“…Four studies included the option of taking the survey online or in-person (Dominguez (2016), Holder & Lange (2014), Montgomery (2014), and Webb, Schaller, & Hunley (2008)). The survey in one study was distributed online only (Hall & Kapa (2015). Interestingly, May and Swabey found that for their multi-site study, participation rates were much higher for surveys distributed in paper format rather than online, and therefore chose to change their distribution model to paper-only for all study sites after the first (p. 774).…”
Section: Resultsmentioning
confidence: 99%